Study Of The Political Dynasty “Native Tenganans” In The Government Of Tenganan Pegringsingan Traditional Village Bali - I Ketut Oka Setiawan; Tetti Samosir (Fakultas Hukum Dehasen, 2024)
The Indonesian state is a unitary state in the form of a republic. Still, in practice, there are dynastic politics of the